Enhancing Walkability for Older Adults: The Role of Government Policies and Urban Design - Akshatha Rao; Rama Devi Nandineni; Roshan S. Shetty; Kailas Mallaiah; Giridhar B. Kamath (Infrastructures)
This research examines the impact of government policy initiatives, community engagement programs, and age-friendly urban design policies on the built environment, with a specific focus on the walkability of older adults. The walkability of older adults in the built environment is essential because it promotes physical activity, social connectedness, and independence, thereby enhancing the overall quality of life and supporting healthy aging. This study employs a quantitative approach and cross-sectional design with convenience sampling in Udupi district, one of the urbanizing districts in India. The sample includes 333 older adults from diverse sociodemographic backgrounds who actively use the built environment. Structural equation modeling was used to test the hypotheses. The findings indicate that community engagement programs are the strongest enabler of safety and security perceptions related to walkability. Safety and security positively correlate with increased physical activity level, increased socialization level, and improved quality of life in older adults. Security also mediates the relationship between community engagement programs and all three outcomes associated with walkability. It highlights priority urban design features such as strategic lighting, sheltered walkways, traffic calming measures, barrier-free access, rest areas, and inclusive design elements as critical components of adaptive urban spaces that promote safety, accessibility, and social inclusion for older adults.